The memoirs of Shamsiah Fakeh from AWAS to 10th regiment - Shamsiah Fakeh 1924-2008
Shamsiah Fakeh was a leader in the independence movement among a group of Malay women who fought persistently right into the jungles of Malaya. She was the head of Angkatan Wanita Sedar (AWAS), which joined forces with Angkatan Pemuda Insaf (API) as flag bearers in the demand for independence from the British. Her collaboration with Ahmad Boestamam, the API head, stoked the spirits of a substantial member of Malayan youths to tak up arms agains the colonisers. Shamsiah also joined the 10th Regiment, the Malay wing of the Malayan Communist Party (MCP). Her life was filled with thorny obstacles. She got lost a few times in the jungle in pursuit of the armed struggle for independence. Her struggle was regardless of place, whether in the jungle or the international arena. She and her husband Ibrahim were sent to China, Indonesia and Vietnam within a framework of inflaming the spirit of nationalism among the people of Southeast Asia who were still colonised then. Shamsiah sacrificed her life and limb to free Malaya through a path that was hers to choose. After she was expelled from the MCP, she stayed on in China and continued her life there working in a ball-bearing factory. She and her family finally returned to Malaysia on 23 July 1994 after the Peace Accords between the MCP and the Malaysian and Thai governments were signed in Haadyai, Thailand, in 1989. Upon her return home, she lived a moderate life in her old age with her children and grandchildren. She never regretted rising against the British and never regretted going into the jungle to join the Communist Party. She was grateful that her struggle had unsettled the colonisers. She believed and was confident that the young generation who understood the true history of the country would be able to find their direction.